2022
DOI: 10.1117/1.nph.9.1.015004
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing reproducibility of cerebral hemodynamic responses when applying short-channel regression in functional near-infrared spectroscopy

Abstract: . Significance: Functional near-infrared spectroscopy (fNIRS) enables the measurement of brain activity noninvasively. Optical neuroimaging with fNIRS has been shown to be reproducible on the group level and hence is an excellent research tool, but the reproducibility on the single-subject level is still insufficient, challenging the use for clinical applications. Aim: We investigated the effect of short-channel regression (SCR) as an approach to obtain fNIRS mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 84 publications
(113 reference statements)
0
26
1
Order By: Relevance
“…All study participants must (1) be at least 18 years old, (2) be native German speakers, and (3) have preferably light and thin hair [ 29 , 30 ]. Participants with a severe cardiac, psychiatric, or neurological disease (eg, epilepsy) or brain injury will be excluded from the study (refer to Multimedia Appendix 1 for details).…”
Section: Methodsmentioning
confidence: 99%
“…All study participants must (1) be at least 18 years old, (2) be native German speakers, and (3) have preferably light and thin hair [ 29 , 30 ]. Participants with a severe cardiac, psychiatric, or neurological disease (eg, epilepsy) or brain injury will be excluded from the study (refer to Multimedia Appendix 1 for details).…”
Section: Methodsmentioning
confidence: 99%
“…The methods improve the ability to measure changes related to NVC 98 , 118 , 126 129 and increase the reproducibility of fNIRS measurements on the single-subject level. 130 …”
Section: Systemic Physiology Augmented Functional Near-infrared Spect...mentioning
confidence: 99%
“…The methods improve the ability to measure changes related to NVC 98,118,[126][127][128][129] and increase the reproducibility of fNIRS measurements on the single-subject level. 130 A comparison between short-channel regression, and SPA-fNIRS-based regression has been recently published by Abdalmalak et al 99 investigating the impact of both methods on the detection and quantification of functional resting-state brain networks. The authors concluded that both approaches are useful and necessary to detect the functional networks and that short-channels and systemic physiological signals "provided complementary information that could not be obtained by either regressor separately."…”
Section: Questions and Answersmentioning
confidence: 99%
“…So far, the most accurate way of removing the extracerebral part of such artifacts is by using the hardware-based solution: shortdistance channels (SDCs). SDCs are generated by placing the source and detector at a distance of < 1 cm, and ideally at ~0.8 cm for adults 72 , to capture the hemodynamic activity from extracerebral tissue only 33,100,[114][115][116][117][118] . SDC signals can be used for correcting the regular distance channels, for instance, by applying a regression-based approach.…”
Section: Systemic Activity Correctionmentioning
confidence: 99%